Effects of the COVID-19 Pandemic on Treatment Outcomes of Drug-Resistant Tuberculosis Patients in Twin Cities of Pakistan: COVID-19 Pandemic on Drug-Resistant Tuberculosis Patients - Bano, Bibi Razia; Pervaiz, Farrah; Mahmood, Humaira; Zulfiqar, Rubab; Samad, Muhammad Zia; Islam, Nazar Ul; Kiyani, Yusra Fatima (Pakistan Journal of Health Sciences, 2025)
Pakistan is the world’s fifth-highest Drug-Resistant Tuberculosis burden region. However, it is difficult to evaluate the setback of COVID-19 when concurrent tuberculosis is excluded in patients from Pakistan, where the national burden of tuberculosis and drug-resistant tuberculosis is substantial and rising despite management efforts. The COVID-19 pandemic is prevalent in countries where tuberculosis, notably drug-resistant tuberculosis is high. Objectives: To compare the pre and para-pandemic favourable and unfavorable outcomes of drug-resistant tuberculosis treatment in PMDT Units of Islamabad and Rawalpindi. Methods: A retrospective cross-sectional study was conducted. The study included Pre and Para-COVID-era drug-resistant tuberculosis patients (n=670) in three sites of Rawalpindi and Islamabad from 2016-2021. A non-probability consecutive sampling technique was applied. A validated structured questionnaire was administered to compare the treatment outcomes of drug-resistant tuberculosis patients. Results: Results show that pre-COVID n=240 (35.82%) and Para-Covid era drug-resistant tuberculosis patients n=226 (33.73%) had favourable treatment outcomes. Unfavorable outcomes before and during the pandemic were 128 (18.35%) and 82 (12.2%) respectively. COVID-19 has affected drug-resistant tuberculosis treatment outcomes, both favourable and unfavorable, which are far behind the treatment success targets set by WHO End-tuberculosis. Conclusions: It was concluded that this study compared drug-resistant tuberculosis treatment outcomes pre- and post-COVID-19, showing success rates surpassing WHO-End tuberculosis targets. Key factors included residential status, gender, and occupation.